Super‐Ionic Conductivity in ω‐Li9TrP4 (Tr = Al, Ga, In) and Lithium Diffusion Pathways in Li9AlP4 Polymorphs. (7th September 2022) - Restle, Tassilo M. F.; Strangmüller, Stefan; Baran, Volodymyr; Senyshyn, Anatoliy; Kirchhain, Holger; Klein, Wilhelm; Merk, Samuel; Müller, David; Kutsch, Tobias; van Wüllen, Leo; Fässler, Thomas F.
Abstract: Phosphide‐based compounds are promising materials for solid electrolytes. In recent times, a multiplicity of compounds featuring isolated M P4 ( M = Si, Ge, Sn, Al, Ga) tetrahedra as structural building units in different arrangements with superionic lithium conductivity have been discovered. ω‐Li9 AlP4, ω‐ Li9 GaP4, and ω‐Li9 InP4 are presented as new high‐temperature modifications with superionic lithium conductivity reaching 4.5 mS cm −1 at room temperature. Impedance spectroscopy and static temperature‐dependent 7 Li NMR experiments reveal conductivity values in the range of 0.2 to 4.5 mS cm −1 at room temperature and low activation energies for the title compounds. X‐ray and neutron diffraction methods disclose that the phosphorus atoms form a cubic‐close packing. The triel element and Li atoms are located in tetrahedral voids, further Li atoms partially fill the octahedral voids. Temperature‐dependent neutron diffraction shows for Li9 AlP4 a phase transition at 573 K that influences the occupation of voids with Li and significantly affects the Li‐ion mobility. The evaluation of nuclear scattering densities by the maximum‐entropy approach and application of the one‐particle‐potential formalism reveal 3D lithium diffusion with a low activation energy preferentially on paths of adjacent tetrahedral and octahedral voids. The investigation of different polymorphs suggests that the equilibrated filling of tetrahedral and octahedral voids is a crucial parameter for the enhancement of superionic lithium conductivity. Abstract : Owing to their superionic lithium ion conductivity and their obvious structural relationships to simple atom packings phosphido‐trielates and phosphido‐tetrelates gain much interest, allowing for a remarkable insight in the structure property relationship of solid ion conductors. The novel superionic compounds ω‐ Li9 Tr P4 ( Tr = Al, Ga, In) complete the series and allow in comparison to their polymorphs to define parameters for good ion conductivity.